2019
DOI: 10.1371/journal.pone.0225515
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of measurement of active trunk movement in wheelchair basketball players

Abstract: The study aim was to assess the reliability to active trunk movements measurement in four sitting positions in wheelchair basketball players and to check their trunk movements in these positions. Eighteen volunteer wheelchair basketball athletes, with a minimum of five years’ training experience, were asked to perform the maximum range of active trunk movement in three planes in four sitting positions (in a sports wheelchair with straps, without straps, on a table with feet on the floor, on a table without foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…Straps are the most used aid for athletes. Thighs and chest straps provide more static and dynamic trunk stability, preventing many falls from the wheelchair 13,14 . Although straps are useful in preventing possible traumatic injuries, it seems that these systems would limit the athletic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Straps are the most used aid for athletes. Thighs and chest straps provide more static and dynamic trunk stability, preventing many falls from the wheelchair 13,14 . Although straps are useful in preventing possible traumatic injuries, it seems that these systems would limit the athletic performance.…”
Section: Discussionmentioning
confidence: 99%
“…MDC is useful to characterize the effectiveness of a device to detect changes in the measured variable and can be calculated using the SEM. When computed at the 90% confidence level ( Kolber et al, 2011 ; Marszałek & Molik, 2019 ; Laird, Kent & Keating, 2016 ), MDC is given by: …”
Section: Methodsmentioning
confidence: 99%
“…To find a consensus between using an easy and feasible method to assess trunk function in all directions (the volume of trunk action), not only in flexion and in extension, and giving some quantitative evidences, we found in the literature that video recording of active trunk movement may be more beneficial than isokinetic trunk measurement to evaluate trunk functions (the volume of action) (Curtis, Kindlin, Reich, & White, 1995;Marszalek & Molik, 2019). Curtis et al (1995) video recorded wheelchair users' trunk movements by two cameras (Curtis et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Curtis et al (1995) video recorded wheelchair users' trunk movements by two cameras (Curtis et al, 1995). Marszałek and Molik (2019) found that the Kinect for Windows V2 sensor can be an easy, valid and reliable device to assess the volume of action of wheelchair basketball players (Marszalek & Molik, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation